Intercultural education and teacher training - Lafuente Guantes, Maria Isabel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This work reflects, from the Philosophy of Education, on the situation of intercultural education in the global society. It is understood that neither philosophy nor the philosopher are exempt from interest, and have part in the turns: cognitive and linguistic. The current situation of this form of education is presented here along with the statement and examination of principles (critical dialogue and cooperative society), purposes (construction of identity, construction of rationality, construction of personality), and actions (social practices), essential for teacher training in this educational modality, as well as the need to include research training in it.